2014
DOI: 10.1121/1.4900561
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave propagation along constant sloped ocean bottoms

Abstract: The nonlinear progressive wave equation (NPE) is a time-domain model used to calculate long-range shock propagation using a wave-following computational domain. Current models are capable of treating smoothly spatially varying medium properties, and fluid-fluid interfaces that align horizontally with a computational grid that can be handled by enforcing appropriate interface conditions. However, sloping interfaces that do not align with a horizontal grid present a computational challenge as application of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The post processor in LS-DYNA has capability to filter out high frequency noise. Eerden and Berg (2010), Gottlied et al (1981), Kleinschmit (2011) and Maestas et al (2014) reported that blast wave contains mainly low frequency content below 125 Hz.…”
Section: Spurious Oscillations In Dynamic Problemmentioning
confidence: 99%
“…The post processor in LS-DYNA has capability to filter out high frequency noise. Eerden and Berg (2010), Gottlied et al (1981), Kleinschmit (2011) and Maestas et al (2014) reported that blast wave contains mainly low frequency content below 125 Hz.…”
Section: Spurious Oscillations In Dynamic Problemmentioning
confidence: 99%